Competition damages actions in the EU : law and practice - Ashton, David (Elgar competition law and practice, 2018)
Competition Damages Actions in the EU offers a clear and concise analysis of the latest legislation and case law, at both EU and national level, in the field of damages actions for breach of EU competition law. This second edition features contributions from practising lawyers in more than ten jurisdictions, as well as offering a thorough analysis of Directive 2014/104. The author explores all aspects of the subject, including substantive problems, such as indirect purchaser standing and passing-on. He examines evidentiary issues, such as access to documents, particularly in the context of leniency programmes, and the probative value of competition authority decisions. Key features of the second edition include: ; First major substantive volume looking at actions for damages under EU competition law since the Commission's proposal, with a thorough review of the Damages Directive of 2014 ; Comprehensive yet accessible text from an experiential viewpoint ; Investigation into the concept of collective action as a politically sensitive phenomenon ; Key section on the quantification of damages in the context of competition law infringements, written by specialist economists. This thorough exposition will be an invaluable resource for practitioners at all levels - from lawyers in private practice, to judges and competition enforcement officials. Being the first to offer a detailed analysis of damages in the context of the new legislation, this book will also appeal to scholars and students of EU competition law.